Socio-psychological aspects of the military aggression in Ukraine: a focal point on women's reproductive health - Sіusіuka, V. H.; M. I. Pavliuchenko; L. P. Shelestova; Сюсюка, Володимир Григорович; Павлюченко, Михайло Іванович; Шелестова, Л. П. (My University, 2025)
The review article analyzes national and foreign scientific researches on the impact of social and-psychological aspects of the military aggression in Ukraine on women’s reproductive health. The relevance of this problem has been studied since the beginning of the aggression in eastern Ukraine and Crimea, when a completely new segment of the population first appeared – internally displaced persons (IDPs). The full-scale invasion in Ukraine, which has been ongoing since February 2022, continues to destroy the lives of civilians and infrastructure, leading to large-scale internal migration and forced departure of the population outside the country. The criticality of the humanitarian catastrophe is confirmed by the fact that by the beginning of 2025, 12.7 million people are in need of humanitarian assistance, and the military aggression has become the largest one in Europe. According to various sources, from 8 to 10 million Ukrainians were forced to leave their homes, including 3.7 million who became IDPs, most of whom are women and children. The analysis of foreign and Ukrainian scientific publications shows that the consequences of traumatic events during war are symptoms of anxiety, depression, post-traumatic stress disorder, which are caused by changes in habitual living conditions, permanent uncertainty, threats to personal safety and the safety of immediate family, loss of loved ones, etc. The data presented confirm that pregnant women are most susceptible to traumatic events and their consequences during hostilities, on whom the war factor can have a critical impact, increasing the risk of adverse obstetric and perinatal consequences. The cessation of the effect of such a significant stress factor on the organism as the military action is impossible before its end, regardless of whether the woman continues to be in her place of permanent residence, has moved to a safer region of the country, or is a refugee who has left the country. This view of the problem confirms the need for a comprehensive approach to diagnosing psychological disorders in pregnant women and requires the immediate need to develop individual programs for medical and psychological support for women during pregnancy. В оглядовій статті проведено аналіз вітчизняних та закордонних наукових досліджень щодо впливу соціально-психологічних аспектів військової агресії в Україні на репродуктивне здоров’я жінок. Актуальність цієї проблеми досліджується з початку агресії у 2014 році на сході України та в Криму, коли вперше з’явився абсолютно новий прошарок населення – внутрішньо переміщені особи (ВПО) з цих регіонів. Повномасштабне вторгнення в Україну, яке триває з лютого 2022 року, продовжує руйнувати життя цивільних людей і інфраструктуру, що призводить до масштабної внутрішньої міграції та вимушеного виїзду населення за межі країни. Критичність гуманітарної катастрофи підтверджується тим фактом, що на початок 2025 року 12,7 млн людей потребують гуманітарної допомоги, а військова агресія стала найбільшою в Європі. За різними даними, від 8 до 10 млн українців були змушені покинути свої домівки, зокрема 3,7 млн стали ВПО, більшість з яких становлять жінки та діти. Аналіз закордонних та вітчизняних наукових публікацій свідчить про те, що наслідками впливу травматичних подій у період війни є симптоми тривоги, депресії, посттравматичного стресового розладу, які зумовлені зміною звичних умов життя, перманентною невизначеністю, загрозою особистій безпеці та безпеці рідних, втратою близьких людей тощо. Наведені дані підтверджують, що найбільш вразливою категорією до впливу травматичних подій та їх наслідків у період бойових дій є вагітні, на яких фактор війни може чинити критичний вплив, підвищуючи ризик несприятливих акушерських і перинатальних ускладнень. Припинення дії такого потужного стресового чинника на організм, як війна, є неможливим до моменту її завершення – незалежно від того, чи йдеться про жінку, яка залишається у місці постійного проживання, переїхала до більш безпечного регіону країни чи стала біженкою за кордоном. Такий погляд на проблему підтверджує необхідність комплексного підходу до діагностики психологічних порушень у вагітних та обумовлює нагальну потребу в розробці індивідуальних програм медико-психологічного супроводу жінок під час вагітності в умовах війни.
Соціально-психологічні аспекти військової агресії в Україні: у фокусі – репродуктивне здоров’я жінок
Keywords: military aggression in Ukraine; social and psychological state; women; pregnancy; consequences of war; stress; anxiety; post-traumatic stress disorder; internally displaced persons; refugees; військова агресія в Україні; соціальний та психологічний стан; жінки; вагітність; наслідки війни; стрес; тривожність; посттравматичний стресовий розлад; внутрішньо переміщені особи; жінки-біженки